University Students’ Behaviours on Single-Use Plastic - Haslina, Hashim (2024)
Plastic waste is an ongoing global crisis because it is polluting the environment and harming the aquatic environment. As a higher education institution, universities are expected to produce citizens who are aware of sustainability practices. The study examines university students’ behaviours on single use plastic. The specific aspects studied are frequency of single-use plastic and management of plastic waste. The participants are 386 students in a university from various disciplines who filled in an online questionnaire. The results indicate that high dependency on single-use plastic mainly for food and drinks packaging because they buy takeaway food. The frequency of single-use plastic is once to three times a day. The participants threw plastic containers and plastic bags into the dustbin. About 90 percent prefer to use single-use plastic containers despite the vendors charging them extra for the containers. The findings suggest availability of single-use plastic packaging and convenience importantly shape students’ high dependency on single-use plastic and their attitudes towards single-use plastic waste management.